TIRZEPATIDE FOR CARDIOVASCULAR RISK REDUCTION: A LITERATURE REVIEW - Elhatra Settaf-Cherif; Layla Settaf-Cherif; Katarzyna Malinowska; Joanna Barwacz; Dagmara Gładysz; Magdalena Adamik (International Journal of Innovative Technologies in Social Science, 2025)
Background: Tirzepatide, a dual glucose-dependent insulinotropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1) receptor agonist, shows promise beyond glycemic control for managing cardiovascular risk factors. Recent studies suggest that tirzepatide may also offer cardiovascular benefits by improving weight, glycemic control, blood pressure, systemic inflammation, and cardiometabolic risk factors. Aim: Our review summarizes the current evidence on tirzepatide’s cardiovascular effects, mechanisms of action, clinical outcomes, and safety profile in populations at increased cardiovascular risk. Methodology: We conducted a narrative literature review of tirzepatide and cardiovascular outcomes using PubMed and Google Scholar. Conclusion: Tirzepatide appears to be a promising therapeutic option for reducing cardiovascular risk, particularly in patients with type 2 diabetes, obesity, and heart failure. Current data support its positive effects on multiple cardiovascular risk factors. However, further confirmation from large clinical trials is needed to fully establish its long-term benefits and safety.